On the Solution of NBVP for Multidimensional Hyperbolic Equations. (25th May 2014) - Ashyralyev, Allaberen; Aggez, Necmettin
Abstract : We are interested in studying multidimensional hyperbolic equations with nonlocal integral and Neumann or nonclassical conditions. For the approximate solution of this problem first and second order of accuracy difference schemes are presented. Stability estimates for the solution of these difference schemes are established. Some numerical examples illustrating applicability of these methods to hyperbolic problems are given.